AI PLATFORMS AND DIGITAL PEDAGOGY IN TEACHING FOREIGN LANGUAGES - Shaxnoza Alikulova; Abdurakhimova Shakhlo Nazirjon qizi; Juraboeva Farangiz Islombek qizi (TADQIQOTLAR, 2026)
Abstract The integration of artificial intelligence (AI) into foreign language education has fundamentally transformed both pedagogical approaches and learning experiences. By enabling  adaptive  learning,  real-time  feedback,  and  personalized  instruction,  AI platforms  offer  new  opportunities  for  enhancing  linguistic  competence.  However, despite  these  advantages,  concerns  remain  regarding  the  reduction  of  human interaction,  overdependence  on  technology,  and  ethical  implications.  This  paper critically examines the role of AI within the framework of digital pedagogy, arguing that  its  effectiveness  depends  on  a  balanced  integration  with  traditional  teaching practices. Ultimately, AI should be viewed not as a replacement for educators, but as a complementary tool that supports more dynamic and learner-centered environments.